Nationwide incidence of lateral malleolar fracture surgery across 6 European countries: has recent evidence changed clinical practice? - PONKILAINEN, Ville; IBOUNIG, Thomas; JONES, Tim; REITO, Aleksi; CRIJNS, Tom J.; WHITEHOUSE, Michael; FELLÄNDER-TSAI, Li; SUTER, Cyrill; RÄMÖ, Lasse; JÄRVINEN, Teppo L. N. (Acta Orthopaedica, 2025)
Background and purpose — Increased use of weightbearing radiographs to assess ankle mortise stability have suggested that most lateral malleolar fractures with a congruent mortise on initial radiographs can successfully be treated nonoperatively. We aimed to evaluate trends in the surgical management of isolated lateral malleolus fractures across Austria, England, Finland, Germany, Sweden, and Switzerland from 2013 to 2022 Methods — We performed a multi-register study to document the annual incidence of operative treatment for isolated lateral malleolus fractures through procedure codes across 6 European countries between 2013 and 2022. The annual incidence of operative treatment was calculated by dividing the total number of procedures per year by the year- and agematched population based on publicly available demographics data. Results — Across the 6 studied European countries, the incidence of surgery for lateral malleolar fracture varied 6-fold between the country with highest (Germany) and lowest (England) incidences; Germany: 37 (95% confidence interval [CI] 37–38) per 105; Switzerland: 34 (CI 32–35) per 105, Austria: 27 (CI 26–28) per 105, Finland: 17 (CI 16–18) per 105, Sweden: 8 (CI 7–9) per 105, and England: 6 (CI 6–7) per 105 in 2021. Over the 10-year study period, the incidence of surgery for lateral malleolar fractures declined notably in Sweden (–29%), Finland (–26%), England (–20%), and Switzerland (–14%), but remained stable in Germany and Austria. Conclusion — The incidence of surgery for lateral malleolar fracture varied 6-fold across 6 studied European countries. Reductions of approximately 20–30% were observed in England, Sweden, and Finland (countries with the lowest baseline rates), while in Germany and Austria (countries with higher baseline rates), the incidence of surgery remained stable over the 10-year observation period.